Implementasi Pembelajaran Sejarah Berbasis dalam Jaringan pada Masa Pandemi Covid-19: Studi Kasus SMAN 1 Rupat Provinsi Riau - Surya Amanda Nababan; Anju Nofarof Hasudungan (Tarikhuna: Journal of History and History Education, 2022)
The Covid-19 pandemic that has plagued the world since its first case was discovered on 17 November 2019 and spread to Indonesia. Covid-19 not only caused casualties but changed the Indonesian education system. The Ministry of Education and Culture of the Republic of Indonesia and the Department of Education in various regions issue instructions to carry out learning that is initially in the classroom and becomes online. Various media such as the Zoom application, WhatsApp group, Google Classroom are used for online learning. The use of various media has become a challenge for history teachers and students, especially for schools in disadvantaged, outermost, and outermost (3T) areas such as SMAN 1 Rupat Bengkalis Regency, Riau Province. The challenge is not to support the internet network, if any, not all students have a smartphone. Even students who have smartphones are not always able to buy internet quota. Evaluation results, the percentage of students present when using; 29, 62 % application zoom, 48, 12% google classroom, and 81, 43% WhatsApp group.